She Asked for It: Hardcore Porn, Sexism, and Rape Myth Acceptance - Borgogna, Nicholas C. (Violence against women, 2022)
The present study examined pornography viewing, rape myth acceptance, and sexist attitudes. Data came from 392 male and 903 female participants. Multigroup SEM indicated neither pornography viewing, nor hardcore pornography viewing, were related to rape myth acceptance when controlling for sexist attitudes among men. Wald tests indicated hostile sexism to be a significantly stronger predictor of all rape myths examined compared to pornography viewing or hardcore pornography viewing in men and women. Latent variable interaction analyses suggested hardcore pornography viewing as a significant exacerbating factor for the relationship between hostile sexism and “she asked for it” rape myths across genders.